Analysis of the Influencing Factors of Students’ Learning Motivation in English - Marlina, Marlina; Muhayyang, Maemuna; Sakkir, Geminastiti (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
This study examines the factors that influence the motivation of grade 11 students to learn English at SMAN 10 Jeneponto. This study used a mixed-methods approach by combining quantitative data and qualitative data. Data were collected through questionnaires completed by 30 students and semi-structured interviews with nine students, selected based on their motivation levels using a purposive sampling technique, to gain deeper insight into their learning experiences. Based on the questionnaire results, students exhibit varying levels of motivation. Namely, 33.33% of students have high motivation, 56.67% have moderate motivation, and 10% have low motivation. Learning motivation is influenced by internal factors, interest in English, self-confidence, personal goals, personal satisfaction, and achievement, and external factors, support from family, peer influence, teaching methods, and school environment. Highly motivated students generally have a great interest in English and receive positive support from their surroundings. In contrast, students with low motivation tend to experience difficulties in understanding the material and lack confidence in using English. Teachers play a crucial role in fostering students’ learning motivation by implementing diverse, engaging, and student-centered teaching methods that align with their needs and learning styles. Therefore, the use of varied teaching methods is recommended to improve students’ motivation in learning English.